Kajian Konsep Ambiguitas Ruang Peralihan Pada Kafe Kekinian di Denpasar dan Badung - Giri, Kadek Risna Puspita (Program Studi Desain Interior Unikom, 2022)
After the government slowly lifted the social distancing restriction since the pandemic in 2020, the growth of